Research on the Location of Front-Loading Warehouses Based on the Reverse Logistics of Fresh Agricultural Products - Jiarui XI; Nana GENG (Promet (Zagreb))
The proposal to create front-loading warehouses has been suggested as a tactic to enhance the effectiveness and quality of distributing fresh agricultural products in the concluding stage of delivery. Nevertheless, there has been a noted escalation in the rate of loss of these products, which can be ascribed to multiple factors, including inaccuracies in demand forecasting. This incongruity arises from consumers’ inability to consume the initially forecasted quantities and unforeseen surges in demand from specific businesses. Consequently, surplus products are left unsold and eventually wasted. This study explores the viability of implementing a reverse logistics model for fresh agricultural products in tandem with the front-loading warehouse. The study presents both traditional and reverse dual models aimed at cost minimisation and introduces novel criteria for the selection of warehouse locations to enhance the efficiency of reverse logistics operations. An advanced hybrid heuristic optimisation algorithm is employed to identify optimal solutions, primarily focusing on minimising product loss rates, reducing logistics expenses and establishing a more equitable supply-demand equilibrium in the area. In the case of Nanjing, it is found that compared with the traditional model, because the network model assumes more functions, the front-loading warehouse in the reverse model has more site selection points in high-demand areas to meet the needs of consumers and is consistent with the distribution of population density and economic activities in Nanjing. At the same time, among the factors affecting the total cost, it is necessary to focus on transportation and fixed costs, while the impact of time and freight damage costs is less.